2013
DOI: 10.4155/fmc.13.71
|View full text |Cite
|
Sign up to set email alerts
|

ABCG2: Recent Discovery of Potent and Highly Selective Inhibitors

Abstract: ABCG2 impacts oral availability, tissue distribution and excretion of its substrates, including anticancer and anti-infectious drugs. Highly expressed at physiological barriers, its secretion level significantly controls drug distribution. Furthermore, its increased content into many types of cancer may lead to cell chemoresistance. Owing to the clinical relevance of ABCG2 in the multidrug resistance phenomenon, ABCG2 constitutes an appealing therapeutic target to increase drug distribution. Development of ABC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 48 publications
1
30
0
Order By: Relevance
“…These three transporters have an extensive overlap in drug specificity offering tumor resistance to the principal classes of chemotherapeutic drugs and molecularly targeted therapies [32,33,173]. Inhibition of ABCG2 transporter activity with phosphodiesterase-5 inhibitors and fumitremorgin-type indolyldiketopiperazine, Ko143, might intensify the efficacy of the chemotherapeutic agents [174,175]. In addition, Martin and colleagues documented that melatonin increases the efficacy of chemotherapeutic agents, targeting both the tumor bulk and brain tumor stem cells (BTSCs) through the regulation of the expression and function of the ABCG2/BCRP transporter by inducing the methylation of its promoter [18].…”
Section: Discussionmentioning
confidence: 99%
“…These three transporters have an extensive overlap in drug specificity offering tumor resistance to the principal classes of chemotherapeutic drugs and molecularly targeted therapies [32,33,173]. Inhibition of ABCG2 transporter activity with phosphodiesterase-5 inhibitors and fumitremorgin-type indolyldiketopiperazine, Ko143, might intensify the efficacy of the chemotherapeutic agents [174,175]. In addition, Martin and colleagues documented that melatonin increases the efficacy of chemotherapeutic agents, targeting both the tumor bulk and brain tumor stem cells (BTSCs) through the regulation of the expression and function of the ABCG2/BCRP transporter by inducing the methylation of its promoter [18].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed, in tumor cell lines, that ABCG2 conferred resistance to various chemotherapeutic drugs, including topotecan (36). However, established tumor cell lines do not always recapitulate ABC transporter expression and function in vivo (37).…”
Section: Discussionmentioning
confidence: 99%
“…They also play a critical role in the induction of multidrug resistance (MDR) in tumor cells [5]. Significant drug discovery efforts have been aimed at developing inhibitors for ABC transporters [6,7], but little is still known about their substrate preference. While recent structural advances have helped close knowledge gaps about the substrate polyspecificity of ABCB1/Abcb1 [8], the lack of detailed structural information about ABCG2/Abcg2 renders the pharmacophore characterization of its substrates more problematic.…”
Section: Introductionmentioning
confidence: 99%